Chronic Diarrhea in Children: Causes, Mechanisms, Primary Diagnostics and Management - Dmitriy V. Pechkurov; Alena A. Tyazheva (Вопросы современной педиатрии, 2020)
The chronic diarrhea is pretty relevant problem in children due to its incidence, wide range of causes, heterogeneity of pathogenetic mechanisms and clinical manifestations. Meantime there is no common algorithm for screening of such patients with chronic diarrhea. This usually aggravates the diagnosis, timely treatment, and finally decreases patient quality of life. This review provides updated data on etiology, pathogenesis, clinical manifestations and diagnostic approaches of chronic diarrhea in children. Issues of structure and management of different diseases manifested in children with chronic diarrhea are considered.